High-speed silicon detector structures for photonic integrated circuits - Ackert, Jason (My University, 2015)
Computing as a service is rapidly becoming the new normal for many sectors of the economy. The widespread availability of broadband internet has allowed an extensive range of services to be delivered on-demand from centralized computing systems known as ‘data centers’. These systems have evolved to be enormously complex. Optical-based communication is desired to increase data center capability and efficiency, however traditional optical technologies are not feasible due to cost and size. Silicon photonics aims to deliver optical communications on an integrated and affordable platform for use in data centers by leveraging the existing capabilities of complementary metal-oxide semiconductor manufacturing. This thesis contains a description of the development of monolithic silicon photodiodes for use in photonic integrated circuits in, and beyond, the current telecommunications wavelength windows. The focus is on methods which are compatible with standard silicon processing techniques. This is in contrast to the current approaches which rely on hybrid material systems that increase fabrication complexity. Chapter 1 and 2 provide background information to place this work into context. Chapter 3 presents an experimental study of resonant devices with lattice defects which determines the refractive index change in silicon-on-insulator waveguides. High-speed operation of resonant photodiodes is demonstrated and is found to be limited by resonance instability. Chapter 4 demonstrates high responsivity avalanche photodetectors using lattice defects. The detectors are shown to operate error-free at 10 Gbit/s, thus confirming their capability for optical interconnects. Chapter 5 presents photodiodes operating with absorption through surface-state defects. These detectors show fast operation (10 Gbit/s) and have an extremely simple fabrication process. Chapter 6 demonstrates photodiodes operating beyond the traditional telecommunications window. Operation at 20 Gbit/s, at a wavelength of 1.96 µm is demonstrated, offering potential for their use in the next generation of optical communication systems which will exploit the thulium doped fiber amplifier.
Keywords: Silicon photonics; photodetectors; integrated optics; optoelectronic devices; silicon-on-insulator; waveguide; lattice defects